Ekonomi Kreatif Home Industry: Pelatihan Pembuatan Shinelime-Sabun Cair Cuci Piring Di Desa Merak Batin Kecamatan Natar - Azmi Farhan Fauzian, Diky Hidayat, R. Supriyanto, Hardoko Insan Qudus, Rinawati, Ni Luh Gede Ratna J (ANDAN JEJAMA: Indonesian Journal of Community Engagement (IJCE), 2022)
Merak Batin Village, Natar District, South Lampung Regency; Natar Inner Peacock Village, Natar District, South Lampung Regency; is not an industrial point area. This is an opportunity for people to think creatively and have new businesses to improve the economy of the community as a whole. One creative business idea that is easy to develop and practice is to make dishwashing liquid soap. Given that liquid dishwashing soap is a household primary need and is very useful and of course in demand in the market, it has the potential to be used as a home industry or home industry. The ingredients needed to make liquid soap solutions are very easy to find on the market and of course, it doesn't require a lot of capital, so the liquid dishwashing soap business will be very promising in the future. Mentoring and training activities are provided by independent KKN students from the University of Lampung period I in 2021. The purpose of this activity is assistance and training in making dishwashing liquid soap for the community so that they have new business opportunities and can be more independent in producing liquid dishwashing soap products of the highest quality. guaranteed quality. The forms of activities carried out are mentoring, training, manufacturing practices, as well as packaging and labeling. The result of this activity is that the community finally has new skills and knowledge about making dishwashing liquid soap